HERDING BEHAVIOR IN THE SHARIA CAPITAL MARKET ON INVESTMENT DECISIONS - Yahya, Adibah; Affandi, Azhar; Herwani, Aldrin; Hermawan, Atang; Suteja, Jaja (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2024)
Herding behaviour is an irrational decision-making because it is the following of other investors. Using information asymmetry as a moderating variable, this research aims at identifying the factors that influenced investment decisions. The research object was the Jakarta Islamic Index, and the data used were quarterly data from 2019 to 2021. The methods of sampling and analysis used were the panel data regression method and the purposive sampling method. The results showed that volatility, exchange rate, market sentiment and firm size positively and significantly affected herding behaviour. Information asymmetry strengthened the influence of herding behaviour on investment decisions. Furthermore, investors and potential investors could use the results to make future investment decisions.